Just be free [compact disc] - Big Freedia (Queen Diva Music, 2014)
The undisputed Queen of Bounce adds to her ever growing fan base with ten tracks about acceptance, love, and embracing differences. The first single, Explode, made its debut on Rolling Stone's website.